The taxonomic and phylogenetic status of some poorly known Anolis species from the Andes of Colombia with the description of a nomen nudum taxon - Grisales-Martínez, Freddy A.; Velasco, Julián A.; Bolívar, Wilmar; Williams, Ernest E.; Daza, Juan M. (Zootaxa, 2017)
We studied the phylogenetic status, morphological variation, dewlap color variation, and geographic distribution of four poorly known Anolis species nested in the Norops clade, particularly in the A. fuscoauratus group from the Andes of Colombia. In addition, we also describe a nomen nudum species based on morphological and molecular evidence. This nomen nudum taxa differ from other fuscoauratoids species in a combination of dewlap color, meristic traits, and molecular evidence. Our integrative analysis (molecular phylogenetics, morphology, and dewlap color) revealed the non-monophyletic status of these Andean taxa. We also confirmed the occurrence of A. fuscoauratus in the Magdalena valley in Colombia (a trans-Andean region). Our findings show that the evolution of Andean anoles is more complex than previously thought and more research is necessary to understand the diversity in this cryptic group.